2019
DOI: 10.1039/c9cc05162g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the gold(i)-catalyzed annulation of propiolates with isoxazoles: a DFT study

Abstract: The detailed mechanisms of gold(i)-catalyzed annulations of propiolates with substituted and unsubstituted isoxazoles were investigated by DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Then the 2M N atom, acting as a nucleophile, attacks the alkyne internal C atom of IM1 due to the greater electron-deficiency of the Please do not adjust margins Please do not adjust margins internal C over the terminal C, as indicated by the calculated NBO charges (0.385e for the former and -0.443e for the latter). Through TS2-3, the necessary Au(III) carbenoid IM3 can then be formed by cleaving the N-O bond 7,8 with a barrier of 10.9 kcal mol -1 . From IM3, C a nucleophilic attack at carbene C will exclusively produce product P a .…”
mentioning
confidence: 99%
“…Then the 2M N atom, acting as a nucleophile, attacks the alkyne internal C atom of IM1 due to the greater electron-deficiency of the Please do not adjust margins Please do not adjust margins internal C over the terminal C, as indicated by the calculated NBO charges (0.385e for the former and -0.443e for the latter). Through TS2-3, the necessary Au(III) carbenoid IM3 can then be formed by cleaving the N-O bond 7,8 with a barrier of 10.9 kcal mol -1 . From IM3, C a nucleophilic attack at carbene C will exclusively produce product P a .…”
mentioning
confidence: 99%
“…49,55 The reason behind similar substrates following different cycloisomerization pathways is yet to be understood despite various experimental 49,57 and theoretical studies. [60][61][62][63][64][65] To probe into the origin of the gold(I)-catalyzed intramolecular regioselectivity of tryptamine-ynamide cycloisomerizations, systematic computational studies using density functional theory (DFT) calculations were carried out in the four studies mentioned above to gain insight into the substrate-dependent mechanisms of these transformations. Our results showed that the non-covalent interactions between the terminal substituent of the alkynyl and the gold(I) catalytic ligand determined the regioselectivity of the reaction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Gold-catalyzed annulations of alkynes with N–O-containing nucleophiles represent efficient and powerful strategies to selectively access versatile carbon- and azaheterocycles . With electron-rich ynamides, gold-catalyzed annulations focus intensely on diverse nitroxy heterocyclic nucleophiles, including isoxazole derivatives, , 1,2,4-oxadiazoles, 4,5-dihydro-1,2,4-oxadiazoles, and 1,4,2-dioxazoles . In addition, electron-deficient propiolates are recently developed as suitable substrates, participating into a series of gold-catalyzed formal annulations of nitroxy heterocycles, among which, 1,2-benzisoxazoles and anthranils are two structurally analogous N,O-functionalized reagents.…”
Section: Introductionmentioning
confidence: 99%